Anana Bicara-Bicara: Selera Musik, Gaya Hidup, dan Strategi Rapper di Kota Jayapura - Anas, Muhammad; Frank, Simon Abdi K.; Idris, Usman (CENDERAWASIH: Jurnal Antropologi Papua, 2020)
Hip Hop music entered Papua, through digital media platforms from the current process of globalization and modernization. For example, through radio, television and the internet. The emergence of Hip Hop music is very loved by young Papuans, especially in Jayapura. The Rap community who works in the field of Hip Hop music is called Anana Bicara-bicara which is part of the urban community subculture in Jayapura. Therefore, this study aims to describe and analyze musical tastes, lifestyles and the artistic strategies of youth who love Hip Hop music in popularizing their existence, warding off stigma and gaining popularity. This study uses a qualitative descriptive method using an ethnographic approach. The research instruments were in the form of voice and image recording devices and field notes for reflection in the field. The technique of determining informants is carried out proposive by optimizing the friendship network. Data collection techniques include in-depth interviews, observation and documentation. Data analysis techniques through the process of data categorization, data description and data interpretation. The results showed that first, the formation of aesthetic tastes from rap music is based on the emotional experiences of each actor. In addition, the rap music structural factor emphasizes the aspect of story telling freely but in orderly rhymes. Second, the lifestyle of rappers in Jayapura follows the trend of Hip Hop music that is Glamorous, Blink-blink, but there are also some who are poorless to show the passion of the ideas they want to convey. Third, the strategy developed is educational, which is to ward off bad stigma about rappers such as making songs that are better and proud of Papua, and creating events that elevate generations. Then, to popularize Hip Hop music through social media Youtube, Facebook, Instagram and WhatsApp.